Measuring enterprises' investments in social capital - a pilot study - Hans Westlund; Elin Nilsson (European Regional Science Association (ERSA), 2003)
Research on the impact of social capital on economic growth has mainly focused on civil society's social capital. The social capital related to enterprises has received little attention. This paper aims at developing a method for measuring enterprises' investments in social capital. We define enterprise-related social capital as social and economic networks in which enterprises intentionally and unintentionally invest and interact in. Certain components of these networks are open for ownership while others are not. Interaction in these networks generates network advantages and economic utility in individual firms as well as in the place/region in which they are located. Based on a division in internal and external social capital, we divide the latter in production-related, environment-related and market-related respectively. We differ between the networks' links and the norms, values, etc that are distributed in the links by the nodes/enterprises. The study is delimited to measurement of the existence and structure of the links. The study shows that it is possible to measure enterprises' investments (in money or time) in social capital. We also found some significant indications on connections between investments in social capital and the enterprises' growth, however without being able to establish any casual relationship. Due to the limited number of participating enterprises these connections are merely indications.
Keywords: 330